The Effect of Health Belief Model Education on Nutrition Behavior of Boys in Secondary Schools in Hamadan - Nahid Mohammadi; Meysam Hooshian; Afsar Omidi; Aliraza Soltanian (Hamadan University of Medical Sciences, 2019)
Introduction: The Adolescents need healthy nutrition education more than any other groups. In present study, the effect of Health Belief Model education on nutrition behavior of secondary boy students was investigated.   Methods: This pre and post test semi-experimental study with two groups was carried out on 120 boys of secondary schools in Hamadan. A randomized cluster sampling method and relative randomize method were used in the first and second stages respectively. At first both groups completed a questionnaire which was based on Health Belief Model and then instructions were given to intervention group in three sessions (45 minutes) on the basis of HBM model. Two months later, data were collected via questionnaires in two groups again. Statistical analysis of the data was performed by SPSS23, the statistical tests were Repeated Measurement ANOVA analysis.   Results: The two groups were similar in demographic characteristics and structure of the HBMModel at the beginning of the study. After the intervention, the mean scores of Health Belief Model structures excepted for the perceived barriers and the average nutritional behavior in the experimental group were more than that of the control group's. In the area of perceived barriers, the mean scores increased in the control group. Repeated Measurement ANOVA showed significant differences between all the domains of the model except for the perceived severity (P<0.05).   Conclusion: According to the results of this study (Health Belief MODEL on Nutrition Behavior) the mean scores increased on the basis of model structures (except for the barriers) after training. So we suggest that health education programs be applied instead of applying traditional instructions.